Active thermal control of water in aircraft combed structures; Defektoskopiya; № 12 - Vavilov V. P. Vladimir Platonovich (2002, 2002)
A technique and equipment of active thermal testing of water in aircraft combed structures ACS are described. The ACS are fabricated from aluminum, glass-reinforced plastic and carbon-filled plastic. Results of simulation and experiments are presented. The limiting possibilities of the active thermal testing are discussed.